The Pervasion of Sexism in Psychiatry - Annie Y. Lei; Taylen O. Arvay (Translation)
Essay Prompt: In the year 2023, the historical impact of bias and sexism on the perception of mental illness is still present in our culture in the United States and world-wide. The passages above may be viewed through that lens, in that Freud and other early psychiatrists tended to blame everything on the mother/woman. Using examples from the passage above, class interviews, optional reading, and/or your own experiences, please write an essay focused on some type of bias (gender, racial, economic, etc) in mental health. Ideas for areas of interest to discuss may be beliefs, perceptions, access to treatment, or consequences of such bias.